A conceptual framework for sustainability in Islamic architecture: the significance of the concepts of man and the environment - Omer, Spahic (Institut Kefahaman Islam Malaysia (IKIM), 2010)
In this paper, I have identified and briefly examined two Islamic concepts which constitute the nucleus of the conceptual framework for sustainability in Islamic architecture. The two concepts are: 1) man as the vicegerent (khalifah) on earth, and 2) natural environment as both a field and means for man’s vicegerency mission. Central to the paper are the following themes: 1) the meaning and significance of Islamic architecture; 2) the position and role of man on earth; 3) peaceful and accountable (sustainable) coexistence with the environment; and 4) the implications of the Islamic concepts of man and the environment for sustainability in Islamic architecture. The paper is concluded by presenting some broad ideas as to the issue of pragmatism in practicing Islamic architecture today. The paper concludes that Islamic architecture is an architecture that through its multidimensionality embodies the message of Islam. It both facilitates the Muslims’ realization of the Islamic purpose and its divine principles on earth and promotes a lifestyle generated by such a philosophy and principles. At the core of Islamic architecture lies function with all of its dimensions: corporeal, cerebral and spiritual. The role of the form is an important one too, but only inasmuch as it supplements and enhances function. Indeed, one of the most recognizable features of Islamic architecture must always be sustainability. This is so because Islam, a comprehensive worldview, ethics and jurisprudence, aims to preserve man and his total wellbeing, i.e., his religion, self, mental strength, progeny (future generations) and wealth (personal, societal and natural).